Relativistic Nuclear Collisions-Photoproduction of $ρ$0 mesons in ultraperipheral heavy ion collisions at energies available at the BNL Relativistic Heavy Ion Collider (RHIC) and CERN Large Hadron Collider (LHC) - Gonçalves, VP; Machado, MVT (Physical Review-Section C-Nuclear Physics, 2009)
n/a
n/a